Bone-Subtraction CT Angiography for the Evaluation of Intracranial Aneurysms - Tomandl, B.F.; Hammen, T.; Klotz, E.; Ditt, H.; Stemper, B.; Lell, M. (American Journal of Neuroradiology, 2006)
PURPOSE: CT angiography (CTA) has been established for detection and therapy planning of intracranial aneurysms. The analysis of aneurysms at the level of the skull base, however, remains difficult because bone prevents a free view. We report initial clinical results of an approach for automatic bone elimination from CTA data.MATERIAL AND METHODS: Before the bone-removal process 2 datasets are acquired: nonenhanced spiral CT with reduced dose and contrast-enhanced CTA. The software automatically registers the nonenhanced data onto the CTA data and selectively removes bone. Vascular structures, as well as brain tissue, remain visible. In this study, we investigated 27 patients with 29 aneurysms, 13 of which were located at the skull base. 3D volume-rendered images with and without bone removal were reviewed and compared with digital subtraction angiography by 2 radiologists in consensus.RESULTS: All supraclinoidal aneurysms were detected on 3D volume-rendered images of both CTA and bone-subtraction CT angiography (BSCTA). Four intracavernous and 3 paraclinoid aneurysms of the internal carotid artery were not visible or were only partially visible on conventional 3D CTA, whereas they could be optimally visualized with BSCTA. Bone removal was successful in all patients; the average additional time for postprocessing was 6.2 minutes. In 7 patients (26%), perfect bone removal without any artifacts was achieved. In most patients, some bone remnants were still present, though it did not disturb the 3D visualization of vascular structures.CONCLUSION: BSCTA allows robust and fast selective elimination of bony structures, thus ascertaining a better analysis of arteries at the level of the skull base. This is useful for both detection and therapy planning of intracranial aneurysms.